Preparing for climate change: an evaluative framework for prioritizing adaptation measures in Nepal - Shrestha, Asheshwor Man (Botanica Orientalis: Journal of Plant Science, 2011)
Severe potential climate threats for Nepal are expected to impact water resource, agriculture, biodiversity and livelihood. While adaptation and mitigation are both valid policy options to tackle climate change, it is advantageous for developing countries to opt for adaptation. It is also desirable that the most feasible adaptation actions be applied to protect development investment from climate risks and to ensure maximum preparedness. Adaptation strategies consist of a set of measures that are highly effective, affordable, technically and socially feasible and contribute towards disaster risk reduction. An evaluative framework using scoring matrix is utilized to prioritize adaptation options. Adaptation options for threat areas identified for Nepal are analyzed based on literature in the context of Nepal as well as for Asia and for least developed countries (LDCs). The measures are evaluated across multiple categories like public/private costs, effectiveness, social/cultural feasibility, speed, support for mitigation and aid in disaster preparedness. Based on the scoring matrix evaluation, following measures appear most feasible: (1) water conservation and management; (2) investment in smaller hydro-power plants; (3) research/planting of climate resistant crops; (4) diversification of agriculture; (5) development of early warning system for disasters; and (6) flood control measures downstream. Due to financial and technical constraints, it is advantageous to opt for ‘no-regrets’ strategies which benefit even without climate change. These set of measures can be carried out at low costs to reap sure benefits and should be prioritized for execution through environmental policies especially climate policies. Key-words: Adaptation; climate change; climate policy; disaster risk reduction; Nepal. DOI: 10.3126/botor.v7i0.4371 Botanica Orientalis – Journal of Plant Science (2010) 7: 35-42